Internalisasi Nilai Kasih Sayang Ibu dalam Pembentukan Karakter Islami Anak: Perspektif Pendidikan Agama Islam - Alihan Satra; Shendi Wahyu Safitri; Andieni Aprilyne Laurensia; Laeli Fitriani; Julia Wulandari; Annisa Zahro (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the internalization of maternal affection in the formation of children's Islamic character from the perspective of Islamic Religious Education. This study is motivated by the important role of the family, particularly the mother, as the first and primary educator in instilling Islamic values ​​from an early age. The method used is library research, examining the Quran, Hadith, and relevant literature on character education and the role of mothers in Islamic education. The results indicate that maternal affection is an effective means of instilling the values ​​of faith, morality, responsibility, discipline, and social concern in children. From the perspective of Islamic Religious Education, the internalization of maternal affection is carried out through role models, habits, advice, attention, and supervision based on Islamic teachings. This process contributes to the formation of Islamic character, reflected in religious attitudes, honesty, independence, and respect for others. Thus, maternal affection plays a strategic role in shaping children's personalities with noble morals and the ability to implement Islamic values ​​in their daily lives.